Respuesta :
Answer:x=−9
Step-by-step explanation:
Apply the distributive property.
3 x + 3 ⋅ 1 − 2 x = − 6
Multiply 3 by 1
.
3 x + 3 − 2 x = − 6
Subtract 2x from 3x.
x + 3 = − 6
Move all terms not containing x to the right side of the equation.
Subtract 3 from both sides of the equation.
x = − 6 − 3
Subtract 3 from − 6 .
x = − 9
3(x+1)-2x=-6
3x+3-2x=-6
(Like terms) 3x-2x=1x
3+1x=-6
-6-3+-9
Now you’re going to divide -9 by 3 which you will get -3
That will be your answer, hope that help you
3x+3-2x=-6
(Like terms) 3x-2x=1x
3+1x=-6
-6-3+-9
Now you’re going to divide -9 by 3 which you will get -3
That will be your answer, hope that help you